Association between triglyceride glucose index and organ involvement in patients with systemic sclerosis - Huidan Yang; Hao Cheng; Huifang Yang; Xiaoying Zhang; Lili Shang; Chenglan Yan; Hongyan Wen (Scientific Reports)
Abstract Patients with systemic sclerosis (SSc) exhibit an elevated risk of multi-organ involvement. Vasculopathy, a hallmark pathological feature of SSc, is closely related to cardiac and renal complications. The triglyceride glucose (TyG) index shows a strong association with vascular injury. In this study, we aimed to investigate the relationship between the TyG index and SSc-related organ involvement and assess its potential predictive value for cardiovascular disease risk. This retrospective cross-sectional study of 102 patients with systemic sclerosis and 89 age- and sex-matched healthy controls were enrolled. The TyG index was calculated by ln [fasting triglycerides (mg/dl) * fasting glucose (mg/dl)/2]. All systemic sclerosis patients were grouped according to the TyG quartile and whether combined with cardiovascular disease. The association between TyG and cardiovascular disease occurrence was evaluated by multivariate regression analysis, restricted cubic spline (RCS), and subgroup analysis. Receiver operating characteristic curves assessed the predictive value of TyG index. Mean TyG index was higher in systemic sclerosis patients versus controls (8.50 $$\:\pm\:$$ 0.45 vs. 8.33 $$\:\pm\:$$ 0.43; P = 0.006). Systemic sclerosis patients with cardiovascular disease or renal involvement had higher TyG index than those without [(8.69 $$\:\pm\:$$ 0.42) vs. (8.39 $$\:\pm\:$$ 0.43), P = 0.001; (8.65 $$\:\pm\:$$ 0.44) vs. (8.45 $$\:\pm\:$$ 0.41), P = 0.044], while patients with joint involvement had lower TyG index [(8.38 $$\:\pm\:$$ 0.44) vs. (8.59 $$\:\pm\:$$ 0.43), P = 0.019]. After grouping according to the TyG quartiles, the incidence of cardiovascular disease and modified Rodnan skin score (mRSS) gradually increased from Q1 to Q4. TyG showed a positive correlation with mRSS score (r = 0.307, P = 0.002). High TyG index was an independent risk factor for cardiovascular disease (OR = 4.03, 95% CI = 1.07–15.10, P = 0.039). TyG index had moderate predictive value for the risk of cardiovascular disease. The TyG index is associated with skin fibrosis and cardiovascular risk in systemic sclerosis and may serve as an effective biomarker for cardiovascular disease risk assessment.